The Structure of the Kikuyu Determiner Phrase Focusing on Modifiers: An X-Bar Theory Perspective - Wahome, Maina; Subiyanto, Agus (PAROLE: Journal of Linguistics and Education, 2023)
This research article investigates the structure of the Kikuyu Determiner Phrase (DP) from an X-bar theory perspective, with a focus on the modifiers of the DP. Kikuyu is a Bantu language spoken by approximately 6.6 million people in Kenya, with a highly agglutinative S-V-O structure. However, limited studies have been conducted on the structure of the Kikuyu DP, which makes this study significant in providing valuable information for researchers and speakers of the language.    The study aims to determine the structure of the Kikuyu DP by analyzing the Kikuyu determiners or modifiers of the noun. In the context of constituent structures, the X-bar theory is employed to depict the varied positions of modifiers within the Determiner Phrase (DP), as evidenced by the phrase structure trees. The research utilizes a descriptive-qualitative method of data analysis, with data collected from resourceful informants and selected Kikuyu texts. The self-introspection method is used, as the researcher is a native speaker of the Kikuyu language. The findings of the study reveal that Kikuyu determiners can be both pre-nominal and post-nominal, with some having the ability to be pre-posed and post-posed like demonstratives. This study contributes to the understanding of the Kikuyu language structure and provides insights for future research.